(دور مؤشر القيمة السوقية في تحقيق كفاءة أسواق رأس المال بالاسقاط على عينة من البورصات العربية (المصرية، السعودية، الاردنية - زنبـط فـايـزة; بكــاي عتيقة; بن عطـاءالله عــائـشة (جامعة عمار ثليجي -الأغواط, 2018)
This study contains an analysis of the efficiency of a sample of the Arab capital markets, economically based on the development of market value. The selection of the Jordan, Saudi Arabia and Egypt Stock Exchange was determined between 1999 and 2008. The study concluded that the Jordanian financial market Is the largest market by market value compared to other markets in the study, while Saudi Arabia is the largest stock market in terms of the contribution of market value to economic growth. Keywords: Efficient, Capital Market, Market Value, Gross Domestic Product, Jordan, Egypt, Saudi Arabia.